Pembelajaran tentang Ekosistem dan Keseimbangan Alam : Meningkatkan Kesadaran Siswa SD tentang Pentingnya Konservasi Alam dan Lingkungan - Farhatun Haya; Khaira Nisa; Rio Febrian Ladipasa; Ari Suriani; Afriza Media (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
Education about ecosystems and environmental balance at the elementary school level plays a crucial role in fostering awareness and environmental care attitudes from an early age. This article examines the effectiveness of ecosystem learning through contextual and project-based learning approaches to enhance students’ understanding and awareness of the importance of maintaining environmental balance. The research method used is a literature study with a qualitative descriptive approach, where data were obtained from various recent journals and books discussing environmental education and conservation in elementary schools. The findings show that learning activities involving direct engagement such as environmental observation, planting, and waste management can strengthen conceptual understanding while building students’ environmental care character. Additionally, the teacher’s role as a facilitator is vital to the success of the learning process. Despite various challenges in implementing environmental education, integrating ecosystem content with character education provides a strong foundation for developing a young generation that is environmentally conscious and responsible for environmental preservation. These findings emphasize the importance of systematically and sustainably implementing ecosystem learning in the elementary school curriculum as a strategic effort towards environmental sustainability.